Adaptability, cohesion and family functionality of nurses during state of emergency by COVID-19 - Sílvia Manuela Dias Tavares da Silva; Carla Sílvia Fernandes; Bruno Miguel Magalhães; Beatriz Edra (Universidad Nacional de Colombia, 2021)
Objective: To evaluate nurses' family adaptability, cohesion, and functionality during the state of emergency. Materials and method: The following is an exploratory, quantitative, descriptive, and cross-sectional study. We used a snowball sample, non-probabilistic, and for convenience. For data collection, we used an instrument consisting of a sociodemographic questionnaire; a family, housing, and cohabitation characterization questionnaire; a Duvall's Family Life Cycle Assessment Scale; a Family Adaptability and Cohesion Evaluation Scale (FACES II); and Family-Scale Adaptation, Partnership, Growth, Affection, and Resolve (APGAR) that measures family function. Results: 125 responses were obtained, being identified the following aspects as predictors of better APGAR, Cohesion, and Adaptability: better housing conditions; families with three or more members; mature families, with children or adult children; individuals teleworking and households in which no more than one member is socially isolated. Age is a predictor of lower adaptability and cohesion. Conclusions: Twenty percent of families (APGAR) have moderate or severe dysfunction; 4.8 % are classified as "extreme" families, and 39.2 % as "very balanced" (FACES II), therefore being at risk.